MAKNA SOSIAL BUDAYA DALAM CITY BRANDING TERNATE KOTA REMPAH - Alhaddad, Yahya (JSPH : Jurnal Sosial Politik Humaniora, 2025)
City branding is not only a communication strategy that plays a crucial role in building a positive image but also in strengthening a city's identity. This study aims to identify, analyze, and examine the socio-cultural meanings of the city branding "Ternate, the Spice City" using a qualitative, descriptive-analytical approach. Data were obtained through in-depth interviews with government officials, traditional leaders, cultural figures, tourism practitioners, and local communities, complemented by participant observation and documentation studies. The analysis was conducted using thematic techniques using Berger & Luckmann's social construction theory framework and Mills' sociological imagination. The results show that the city branding "Ternate, the Spice City" functions not only as a tourism promotion strategy but also as a collective identity construct that connects the history of the spice trade with contemporary life. This branding evokes collective memory through visual symbols, festivals, culinary delights, and public narratives that affirm Ternate as a global heritage. Community participation is realized through deliberative forums, digital public spaces, and the involvement of MSMEs and local communities. Local media plays a role in maintaining the legitimacy of branding while bridging the gap in access to information. Despite challenges such as limited participation among island communities, a more inclusive strategy can strengthen a sense of belonging and social cohesion. Thus, “Ternate, the City of Spices” becomes a model of city branding that not only builds a national and international image, but also provides real benefits for the welfare of the community and strengthens socio-cultural identity.